Mapping the knowledge landscape: A bibliometric analysis of exosome research in osteoarthritis (2004–2023) - Hui Xu; Zhen Wang; Zheng Wang; Juntao Chen; Chi Zhao; Bingxin Kang; Xirui Xu; Jun Shen; Mengmeng Li; Jieyao Diao; Jun Xie; Lianbo Xiao (Heliyon)
Exosomes have emerged as a crucial focus in advancing the diagnosis and treatment of osteoarthritis (OA). However, there are limited bibliometric studies on this topic. This study aimed to delineate the literature landscape on exosomes in OA, identifying global research trends and key areas. We utilised the Web of Science Core Collection to retrieve articles published from 2004 to 2023. Our analysis included 456 publications across 671 institutions from 40 countries/regions. Publication volume, citations, and emerging research foci and trends were examined. Our results reveal a consistently increased interest in exosomes related to OA over the past two decades. Prominent institutions contributing to this research include Shanghai Jiao Tong University and Shenzhen University. The leading journal for these publications is the International Journal of Molecular Sciences, with Stem Cell Research & Therapy being the most frequently co-cited journal. Notable scholars in this field are Li Duan, Yujie Liang, Xiao Xu, and Wei Seong Toh, with Shipin Zhang emerging as the most co-cited author. The principal research themes were elucidating how exosomes contribute to OA pathology and developing novel therapeutic approaches. Research hotspots and new trends are linked to terms such as “cartilage,” “mesenchymal stem cell,” “miRNA,” “treatment,” and “biomarkers.” This comprehensive analysis offers valuable insights into the prevailing scientific discourse, pivotal topics, and potential future directions. It could serve as a foundational reference for researchers exploring exosomes and their utility in OA diagnostics and therapeutics.